Law through the life course - Herring, Jonathan (Bristol : Bristol University Press, 2021)
This text explores the interactions of the law with the life course in order to understand the complex life journey as a whole. Jonathan Herring reveals how the law privileges 'middle age' to the detriment of the whole life story and explains why an understanding of the life course is important for lawyers.
Also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 10, 2021).
Keywords: Law; Life cycle, Human; Law; Jurisprudence & general issues